Impact of an Australian/New Zealand organisational position statement on extended‐release opioid prescribing among surgical inpatients: a dual centre before‐and‐after study. (5th May 2021) - Awadalla, R.; Liu, S.; Kemp‐Casey, A.; Gnjidic, D.; Patanwala, A.; Stevens, J.; Begley, D.; Bugeja, B.; Penm, J.
Summary: Extended‐release opioids are often prescribed to manage postoperative pain despite being difficult to titrate to analgesic requirements and their association with long‐term opioid use. An Australian/New Zealand organisational position statement released in March 2018 recommended avoiding extended‐release opioid prescribing for acute pain. This study aimed to evaluate the impact of this organisational position statement on extended‐release opioid prescribing among surgical inpatients. Secondary objectives included predictors and clinical outcomes of prescribing extended‐release opioids among surgical inpatients. We conducted a retrospective, dual centre, 11‐month before‐and‐after study and time‐series analysis by utilising electronic medical records from two teaching hospitals in Sydney, Australia. The primary outcome was the proportion of patients prescribed an extended‐release opioid. For surgical patients prescribed any opioid (n = 16, 284), extended‐release opioid prescribing decreased after the release of the position statement (38.4% before vs. 26.6% after, p < 0.001), primarily driven by a reduction in extended‐release oxycodone (31.1% before vs. 14.1% after, p < 0.001). There was a 23% immediate decline in extended‐release opioid prescribing after the position statement release (p < 0.001), followed by an additional 0.2% decline per month in the following months. Multivariable regression showed that the release of the position statement was associated with a decrease in extended‐release opioid prescribing (OR 0.54, 95%CI 0.50–0.58). Extended‐release opioid prescribing was also associated with increased incidence of opioid‐related adverse events (OR 1.52, 95%CI 1.35–1.71); length of stay (RR 1.44, 95%CI 1.39–1.51); and 28‐day re‐admission (OR 1.26, 95%CI 1.12–1.41). Overall, a reduction in extended‐release opioid prescribing was observed in surgical inpatients following position statement release.